Application of dividend discount model valuation at Macedonian Stock Exchange - Zoran Ivanovski; Nadica Ivanovska; Zoran Narasanov (UTMS Journal of Economics, 2015)
Dividend discount model (DDM) is the simplest model for valuing equities in finance. Many analysts belived that DDM is outmoded, but much of the intuition that drives Discounted Cash Flow (DCF) valuation is embedded in the DDM model. There are also specific companies stocks where the DDM model remains a useful tool for estimating value. The basic task of these research is to examine if DDM models offer relevant and safe valuation of long-term securities at Macedonian Stock Exchange (MSE) through the process of empirical valuation of random chosen stocks. This research helped us to identify problems in use of DDM valuation models at MSE, to determine causes for differences between the intrinsic values and the stock market prices and to determine basic parameters for implementation of valuation on Macedonian financial market. We find that DDM models are usefull only as additional tool beside relative and DCF stocks valuation at MSE.
Keywords: G1; G12; 330; valuation; securities; free cash flow; dividends; equity